Ultrasound of the lung - Dietrich, Christoph F.; Görg, Christian; Horn, Rudolf; Prosch, Helmut; Safai Zadeh, Ehsan; Jenssen, Christian (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
The CME review is intended to explain and discuss the clinical value of lung ultrasound but also to enable a pragmatically oriented approach by analyzing the clinical aspect. This includes knowledge of the pre-test probability, the acuteness of the disease, the current clinical situation, detection and/or characterization, initial diagnosis or follow up assessment and the peculiarities of exclusion diagnosis. Diseases of the pleura and lungs are described using these criteria with their direct and indirect sonographic signs and the specific clinical significance of ultrasound findings. The importance and criteria of conventional B-mode, color Doppler ultrasound with or without spectral analysis of the Doppler signal and contrast-enhanced ultrasound are discussed as well.
Keywords: pleural effusion; pneumonia; guideline; lung embolism